The Role Of Organizational Innovation: A Study Of Tourism Villages In Magelang, Indonesia - Dian Marlina Verawati; Suharnomo Suharnomo; Indi Djastuti (Jurnal Manajemen, 2023)
The increasing number of new tourist attractions and corrent tourism trends are forcing tourist villages to think about developing throungh innovation. Data were collected through questionnaires and analyzed using the structural equation model (SEM)-Amos to test the model quantitatively with 115 respondents. This study concludes that transformational leadership is a source of creativity in the context of rural tourism leadership. Knowledge management is an important resource to survive and follow trends amidst the shocks of the proliferation of new tours. Innovation is essential for the resilience of tourist villages and survival strategies. Transformational leadership and knowledge management have a positive and significant effect on organizational innovation; organizational innovation strengthens and significantly and positively influences the relationship between transformational leadership and knowledge management, influencing organizational performance. Transformational leadership and knowledge management positively and significantly affect organizational performance.